1997
DOI: 10.1074/jbc.272.6.3153
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Substrate Specificity of Meprin β on the Basis of the Site in Protein Kinase A Cleaved by the Kinase Splitting Membranal Proteinase

Abstract: The kinase splitting membranal proteinase (KSMP) is a metalloendopeptidase that inactivates the catalytic (C) subunit of protein kinase A (PKA) by clipping off its carboxyl terminal tail. Here we show that this cleavage occurs at Glu 332 -Glu 333 , within the cluster of acidic amino acids (Asp 328 -Glu 334 ) of the kinase. The K m values of KSMP and of meprin ␤ (which reproduces KSMP activity) for the C-subunit are below 1 M. The K m for peptides containing a stretch of four Glu residues are in the micromolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Both samples were subjected to SDS-PAGE (7.5% gels with ␤-mercaptoethanol), followed by immunoblotting using anti-mouse meprin ␣ polyclonal antibodies. B, the amount of meprin ␣ protein per microliter in both the cell lysates and the media was determined by densitometric scans of immunoblots using laser densitometry as described previously (12). The data are shown as the mean Ϯ S.E.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both samples were subjected to SDS-PAGE (7.5% gels with ␤-mercaptoethanol), followed by immunoblotting using anti-mouse meprin ␣ polyclonal antibodies. B, the amount of meprin ␣ protein per microliter in both the cell lysates and the media was determined by densitometric scans of immunoblots using laser densitometry as described previously (12). The data are shown as the mean Ϯ S.E.…”
Section: Resultsmentioning
confidence: 99%
“…They are capable of degrading proteins such as collagen and gelatin, hormones such as parathyroid hormone, luteinizing hormone-releasing hormone, and melanocyte-stimulating hormone, and small peptides such as bradykinin, angiotensins, and gastrin (11,12). The meprins may, therefore, be involved in activation or inactivation of important extracellular proteins and peptides, and are highly regulated at transcriptional and posttranscriptional levels themselves.…”
mentioning
confidence: 99%
“…Meprins are capable of degrading proteins such as collagens and gelatin; hormones such as parathyroid hormone, luteinizing hormone-releasing hormone, and melanocyte-stimulating hormone; and small peptides such as bradykinin, angiotensins, and gastrin (3,11). The meprins may therefore be involved in activation or inactivation of important extracellular proteins and peptides and are highly regulated at transcriptional and post-transcriptional levels themselves.…”
mentioning
confidence: 99%
“…Previous studies have shown that a variety of biologically active peptides and proteins are hydrolyzed by meprins in vitro. For example, meprins cleave blood pressure regulators such as bradykinin, metabolism mediators such as parathyroid hormone, signaling molecules such as protein kinase A, and basement membrane proteins such as entactin (1,2,16,17). There has been no systematic study, however, of the enzymatic differences between meprin A and B from any species or of the contributions of the individual subunits to activity.…”
mentioning
confidence: 99%